Pelatihan Akuntansi Satuan Kerja Perangkat Daerah (SKPD) Siswa Jurusan Akuntansi SMK Negeri 1 Godean - Yanto Darmawan; Rahimah Rahimah; Tio Waskito Erdi; Muhammad Umroh (Jaanur Elbarik Indonesia, 2026)
This community service activity was designed to enhance the understanding and practical skills of students at SMK Negeri 1 Godean in applying accrual-based regional government accounting. The Guest Lecturer Program was conducted on 15–16 October 2025 in collaboration with YKPN Polytechnic Yogyakarta and involved 108 students from the Accounting and Institutional Finance Department. The program consisted of four main sessions: a pre-test, in-depth theoretical instruction, hands-on practice in recording SKPD accounting transactions, and a post-test. In addition, students gained direct practical experience in preparing SKPD financial statements and demonstrated improvements in accuracy and teamwork. Overall, the activity effectively strengthened collaboration between higher education institutions and vocational schools as an implementation of the link and match concept in vocational education.